Effect of surface treatment on epoxy resin adhesion between structural steel y unidirectional carbon fiber) - Tigmasa, Luis (2025)
Currently, technology has enabled the development of alternative materials that, in certain applications, replace conventional materials. One of these materials is unidirectional carbon fiber, which is used to reinforce existing structures, whether made of steel or concrete. The bonding medium between carbon fiber and steel is epoxy resin. Specifically, in steel structures, adhesion issues have been detected at the steel-epoxy resin interface. Different types of surface cleaning treatments applied to the steel are used to determine the degree of adhesion at the interface between the epoxy resin and structural steel through tensile tests on simple lap joints. It was identified that roughness is a key variable in joint strength. To modify roughness, different surface cleaning methods were applied, resulting in various roughness levels. The best results for adhesion strength were obtained with the cleaning treatments using a steel-bristle disc and shot blasting. Through this research, the adhesion strength for practical applications in steel structure reinforcement was determined.